Qol Tamid The Shofar in Ritual, History, and Culture - Friedmann, Jonathan L.; Gereboff, Joel (Claremont Studies in Hebrew Bible and Septuagint, 2017)
An examination of the role of the Shofar (Ram's Horn) in Jewish life from antiquity to the current time.